2016
DOI: 10.1371/journal.ppat.1005624
|View full text |Cite
|
Sign up to set email alerts
|

IL-26: An Emerging Proinflammatory Member of the IL-10 Cytokine Family with Multifaceted Actions in Antiviral, Antimicrobial, and Autoimmune Responses

Abstract: International audienceCytokines are small proteins that mediate signaling in immune and nonimmune cells, resulting in the modulation of cellular differentiation and activation. These functions are not only important for inflammation but also for antimicrobial responses. Additionally, inflammatory cytokines such as IL-1β and IL-17 can directly interact with microbes and promote their growth [1,2]. In this context, IL-26, an emerging member of IL-10 family cytokines, stands distinct as it exerts antimicrobial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…55 The IFN-like cytokines (IL-26 and IL-29) secreted by T17 cells also activate STAT1 in keratinocytes leading to the expression of CXCL9, CXCL10, and CXCL11 which attract Th1 cells into psoriatic skin and sensitize keratinocytes to its own action. 56, 57 Psoriatic keratinocytes also synthesize other growth factors which affect connective tissue cells in the dermis; platelet-derived growth factor (PDGF), angiopoietin-2, and vascular endothelial growth factor (VEGF) likely drive angiogenesis, which accounts for the erythematous skin lesions. 58 …”
Section: The Pivotal Role Of Il-17 In Updated Disease Models Of Psorimentioning
confidence: 99%
“…55 The IFN-like cytokines (IL-26 and IL-29) secreted by T17 cells also activate STAT1 in keratinocytes leading to the expression of CXCL9, CXCL10, and CXCL11 which attract Th1 cells into psoriatic skin and sensitize keratinocytes to its own action. 56, 57 Psoriatic keratinocytes also synthesize other growth factors which affect connective tissue cells in the dermis; platelet-derived growth factor (PDGF), angiopoietin-2, and vascular endothelial growth factor (VEGF) likely drive angiogenesis, which accounts for the erythematous skin lesions. 58 …”
Section: The Pivotal Role Of Il-17 In Updated Disease Models Of Psorimentioning
confidence: 99%
“…immune responses (23)(24)(25)(26). We evaluated the levels of these molecules in the serum of 64 patients, to test whether pathogen-reactive neoplastic B cells are specifically associated with inflammation and infection.…”
Section: Patient Characteristics and Serological Statusmentioning
confidence: 99%
“…IL-22 can be co-expressed with interferon (IFN)-γ in Th1 cells and with IL-17A in Th17 cells [4, 8], however more recent studies identified Th22 cells, which only produce IL-22 but not IFN-γ or IL-17A [9, 10]. IL-26 is expressed only in humans but not in mice, and its main cellular sources include Th1 and Th17 cells, NK cells and alveolar macrophages [1, 11]. The biological effects of IL-20 subfamily plays a critical role in host defense, tissue protection and regulation of autoimmune response.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, IL-22 is the most studied cytokine because it acts as the effector cytokine of Th17 and Th22 cells, as well as several lineages of innate lymphoid cells [4, 17, 18]. The biological functions and the association in human diseases of the broader IL-20 subfamily have been reviewed previously [1, 4, 11, 17, 19]. However, most of them only focus on IL-22, while the discussion on the roles of IL-20R cytokines in immunoregulation is limited.…”
Section: Introductionmentioning
confidence: 99%